2008
DOI: 10.1007/s10616-008-9170-z
|View full text |Cite
|
Sign up to set email alerts
|

Chickpea protein hydrolysate as a substitute for serum in cell culture

Abstract: The growth of mammalian cells in vitro requires the use of rich culture media that are prepared by combining serum with specific nutrient formulations. Serum, the most expensive component of culture media, provides a complex mixture of growth factors and nutrients. Protein hydrolysates that can support in vitro cell growth and eliminate or reduce the need to use serum have been obtained from different sources. Here we describe the use of two food grade proteases to produce a chickpea protein hydrolysate that h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 36 publications
1
20
0
Order By: Relevance
“…Thus, THP-1 cells kept growing after 20 passages when cultured in medium supplemented with alcalase-flavourzyme hydrolysate in the absence of serum, but Caco-2 cells did not grow at all (Giron-Calle et al, 2008). Nevertheless, no correlation could be found between the long-term and short-term effects on growth in the absence of serum.…”
Section: % Fbsmentioning
confidence: 88%
See 3 more Smart Citations
“…Thus, THP-1 cells kept growing after 20 passages when cultured in medium supplemented with alcalase-flavourzyme hydrolysate in the absence of serum, but Caco-2 cells did not grow at all (Giron-Calle et al, 2008). Nevertheless, no correlation could be found between the long-term and short-term effects on growth in the absence of serum.…”
Section: % Fbsmentioning
confidence: 88%
“…Thus, proliferation of THP-1 cells was actually inhibited by up to 100% in cultures exposed to hydrolysates with various DH for up to 3 days. In the presence of serum, proliferation of Caco-2 cells was inhibited by up to 30% under certain conditions, while proliferation of THP-1 cells was actually promoted by up to 100% in the presence of 0.5% FBS, and no effect on proliferation was observed when the THP-1 cells were exposed to hydrolysates in the presence of 10% FBS (Giron-Calle et al, 2008). Comparing these results with the present study, it should be concluded that although enzymatic hydrolysis of chickpea protein using either microbial or physiological enzymes produces growth-promoting and growth-inhibiting peptides, the activity profile of hydrolysates with the same DH produced with either type of enzymes is not the same.…”
Section: % Fbsmentioning
confidence: 95%
See 2 more Smart Citations
“…A related study reported on the production of hydrolysates of chickpeas by microbial proteases; the obtained peptides promoted the proliferation of human monocyte THP-1 cells but inhibited the proliferation of Caco-2 cells. 130 Subsequently, the authors evaluated the effect of hydrolysates obtained with pepsin and pancreatin on the proliferation of THP-1 and Caco-2 cells. The hydrolysates inhibited the proliferation of Caco-2 cells up to 45% and of THP-1 cells up to 78%.…”
Section: Immunomodulatory Peptides Derived From Plant Proteinsmentioning
confidence: 99%